Trends in gabapentinoid prescribing in patients with osteoarthritis: a United Kingdom national cohort study in primary care. Issue 10 (October 2019) - Appleyard, T.; Ashworth, J.; Bedson, J.; Yu, D.; Peat, G.
Summary: Objective: To investigate trends in gabapentinoid prescribing in patients with osteoarthritis (OA). Methods: Patients aged 40 years and over with a new OA diagnosis recorded between 1995 and 2015 were identified in the Clinical Practice Research Datalink (CPRD) and followed to first prescription of gabapentin or pregabalin, or other censoring event. We estimated the crude and age-standardised annual incidence rates of gabapentinoid prescribing, stratified by patient age, sex, geographical region, and time since OA diagnosis, and the proportion of prescriptions attributable to OA, or to other conditions representing licensed and unlicensed indications for a gabapentinoid prescription. Results: Of 383, 680 newly diagnosed OA cases, 35, 031 were prescribed at least one gabapentinoid. Irrespective of indication, the annual age-standardised incidence rate of first gabapentinoid prescriptions rose from 1.6 [95% confidence interval (CI): 1.3, 2.0] per 1000 person-years in 2000, to 27.6 (26.7, 28.4) in 2015, a trend seen across all ages and not explained by length of follow-up. Rates were higher among women, younger patients, and in Northern Ireland, Scotland and the North of England. Approximately 9% of first prescriptions could be attributed to OA, a further 13% to comorbid licensed or unlicensed indications. Conclusion: Gabapentinoid prescribing in patients with OA increased dramatically between 1995 and 2015. In most cases, diagnostic codes for licensed or unlicensed indications were absent. Gabapentinoid prescribing may be attributable to OA in a significant proportion but evidence for their effectiveness in OA is lacking. Further research to investigate clinical decision making around prescribing these expensive and potentially harmful medicines is recommended.